LncRNA MALAT1 mediates osteogenic differentiation in osteoporosis by regulating the miR-485-5p/WNT7B axis - Zhou, Yuan; Xu, Zhuo; Wang, Yuanyi; Song, Qiang; Yin, Ruofeng (Frontiers in Endocrinology, 2023)
Accumulating evidence demonstrates that long non-coding RNAs (lncRNAs) are associated with the development of osteoporosis. This study aimed to investigate the effects of MALAT1 on osteogenic differentiation and cell apoptosis in osteoporosis. MALAT1 level, detected by RT-qPCR, was downregulated in hindlimb unloading (HU) mice and simulated microgravity (MG) treated MC3T3-E1 cells. Moreover, osteogenic differentiation-related factors (Bmp4, Col1a1, and Spp1) levels were measured by RT-qPCR and western blot. ALP activity was detected, and ALP staining was performed. Cell apoptosis was assessed by flow cytometry. The results revealed that MALAT1 upregulated the expression of Bmp4, Col1a1, Spp1, and enhanced ALP activity. Knockdown of MALAT1 suppressed their expression and ALP activity, suggesting MALAT1 promoted osteogenic differentiation. Additionally, MALAT1 inhibited apoptosis, increased Bax and caspase-3 levels, and decreased Bcl-2 level. But knockdown of MALAT1 got the opposite results. In MG cells, MALAT1 facilitated osteogenic differentiation and suppressed apoptosis. Furthermore, miR-485-5p was identified as a target of MALAT1, and WNT7B was verified as a target of miR-485-5p. Overexpression of miR-485-5p rescued the promotion of osteogenic differentiation and the inhibition of apoptosis induced by MALAT1. Knockdown of WNT7B abolished the facilitation of osteogenic differentiation and the suppression of apoptosis induced by downregulation of miR-485-5p. In conclusion, MALAT1 promoted osteogenic differentiation and inhibited cell apoptosis through miR-485-5p/WNT7B axis, which suggested that MALAT1 is a potential target to alleviate osteoporosis.